Toolbox for adopting computational thinking through learning Flash - Saari, Erni Marlina (2018)
The need for teachers of Elementary School children to learn to program or rather to understand the Computational Thinking behind programming has been accelerated in many countries by the mandated teaching of programming in the Elementary School context. Many steps have been taken in order to create awareness of this issue, such as the Computing At Schools initiative (CAS) which is established in the UK. CAS aims to support teaching in computing and connected fields in UK schools. Moreover, in the USA the Computer Science Teachers Association (CSTA) was established to meet the purpose of informing and advising about the current development of computational thinking and to investigate and disseminate teaching and learning resources related to computational thinking. In Singapore research has been conducted by the government agency Infocomm Development Authority of Singapore (IDA) whereby the major goal is to meet the needs in the ICT sector and ultimately to focus and inspire learners about programming.